Pengaruh Excess Control terhadap Cost of Capital dalam Meningkatkan Profitabilitas - Hendra Gunawan; Rani Yessi Sinaga (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
This study examines the effect of excess control on cost of capital seen from the profitability of the company to prove its effect on increasing the profitability of manufacturing companies. This study uses secondary data taken from the auditor's financial statements. The results show that excess control has a positive effect on cost of capital. The results of this study illustrate that capital will be good for the company if the funds are used effectively and efficiently. This research is important for companies and organizations, in order to be better in the use or utilization of capital in the company's operations. This company is only limited to manufacturing companies, so the next research is expected to be able to use samples from other industries.